Tendințe de europenizare a administrației publice locale - Slusarenco, Svetlana (Print-Caro, 2023)
The status of a candidate country for joining the European Union is an opportunity for the Republic of Moldova to reflect on the progress achieved and to ensure our common commitment to improving and sharing common European values. Joining the European Union is an opportunity, but it is also a responsibility. With a view to joining the European Union and aligning the national regulatory framework with European standards regarding central and local public administration, numerous public policy acts were adopted, which describe the vision, purpose, objectives, actions and resources necessary for the process of transformation/improvement of public administration from the Republic of Moldova at central and local level. The process of adopting a new regulatory framework favors compliance actions at the national, local level.

Statutul de țară candidată la aderarea la Uniunea Europeană, constituie o oportunitate pentru Republica Moldova de a reflecta asupra progresului obținut și de a ne asigura angajamentul comun pentru îmbunătățirea și împărtășirea valorilor comune europene. Aderarea la Uniunea Europeană este o oportunitate, dar este și o responsabilitate. În vederea aderării la Uniunea Europeană și alinierii cadrului normativ national la standardele europene privind administrația publică centrală și locală, au fost adoptate numeroase acte de politici publice, care descriu viziunea, scopul, obiectivele, acțiunile și resursele necesare procesului de transformare/perfecționare al administrației publice din Republica Moldova la nivel central și local. Procesul de adoptare a unui nou cadru de reglementări favorizează acţiuni de conformitate la nivel naţional, local.
Keywords: accession; opportunity; regulatory framework; European standards; local administration; public services; aderare; oportunitate; cadru normativ; standarde europene; administrația locală; servicii publice